2013
DOI: 10.1039/c3ob40249e
|View full text |Cite
|
Sign up to set email alerts
|

Peptide inhibitors of the Keap1–Nrf2 protein–protein interaction with improved binding and cellular activity

Abstract: Inhibitors of the Keap1-Nrf2 protein-protein interaction (PPI) have been proposed as potential anti-inflammatory and cancer chemopreventive agents. Such compounds have the potential to increase the intracellular concentrations of Nrf2 in a reversible manner and consequently increase the expression of a battery of gene products with antioxidant response elements (AREs) in their promoter region. In this manuscript we describe the development of peptide inhibitors with modified C- and N-termini and reduced overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 21 publications
2
88
0
Order By: Relevance
“…Basic structural compositions in the design of peptide inhibitors are summarised as follows (Hancock et al 2013):…”
Section: Peptide Inhibitorsmentioning
confidence: 99%
“…Basic structural compositions in the design of peptide inhibitors are summarised as follows (Hancock et al 2013):…”
Section: Peptide Inhibitorsmentioning
confidence: 99%
“…The minimal peptide sequence with inhibitory capacity was the 9-mer sequence of LDE-ETGE-FL (Chen et al, 2011;Inoyama et al, 2012). In parallel, Wells and collaborators (Hancock et al, 2013) searched for new putative peptide ligands using a phage display library combined with high-throughput fluorescence polarization assay. They found that hybrid peptides based upon the ETGE motif of NRF2 and SQSTM1 have superior binding activity to KEAP1 compared with either native peptide alone.…”
Section: B Protein-protein Interaction Inhibitors For Nuclear Factormentioning
confidence: 99%
“…Both approaches result in peptides that up-regulate Nrf2-dependent gene products in cells [haeme oxygenase-1 (HO1) in monocytic leukaemia (THP-1) cells in the case of the TAT conjugates, NAD(P)H quinone oxidoreductase-1 (NQO1) in Hepa1c1c7 cells in the case of the steric acid conjugate (J)]. However, this activity is manifested at mid-micromolar peptide concentrations despite the steric acid conjugate J binding to Keap1 with an IC 50 of 22 nM [33]. This indicates that cell entry is very inefficient and that there is considerable scope for improving the cell-based activity of peptides by approaches that reduce or mask the net charge of the sequences or facilitate cell entry.…”
Section: Peptide Inhibitorsmentioning
confidence: 93%
“…However these short peptides are very polar and do not display significant Nrf2 inducing activity in cells. There have been attempts to address this lack of activity by conjugating the ETGE sequences to cell penetrating TAT peptide sequences and by conjugation to fatty acids [33,34]. Both approaches result in peptides that up-regulate Nrf2-dependent gene products in cells [haeme oxygenase-1 (HO1) in monocytic leukaemia (THP-1) cells in the case of the TAT conjugates, NAD(P)H quinone oxidoreductase-1 (NQO1) in Hepa1c1c7 cells in the case of the steric acid conjugate (J)].…”
Section: Peptide Inhibitorsmentioning
confidence: 99%